Nursing care in the care of autist children: integrative review (Research, Society and Development, 2023)
• Introduction: The present work has as its theme nursing care for autistic children, in which it was proposed to discuss the importance of nursing children with ASD. Autism is a developmental disorder that usually involves children before the age of three, pointing out repetitive and restricted behavior as some of its characteristics, and the impairment of motor and psychoneurological development, which hinders the child's cognition, communication, language and social interaction. Objective: To describe the nursing care provided to autistic children. Methodology: The present study used the integrative review as a method, since it is the broadest method compared to bibliographic review studies, which aims to gather and summarize the scientific knowledge already produced on the subject investigated between the years 2009 to 2022. Results: It was possible to find obstacles that could compromise the characteristic and effectiveness of assistance to this public in the first care, such as: the lack of coordination of responsibility, the lack of time and practice guidelines, in addition to the deficit in qualification to care of autistic children, as well as investments in professional skill, planning and development of protocols and guidelines that guide the clinical practice of care. Conclusion: It was concluded that there is little information on the subject and little experience and recognition of health professionals in assisting autism. For this, there is a great lack of updating in studies and investigations that contribute to the development and expansion of the clinical view of nursing care with these patients.